2014
DOI: 10.1213/ane.0000000000000411
|View full text |Cite
|
Sign up to set email alerts
|

Catechol-O-Methyltransferase Polymorphisms Predict Opioid Consumption in Postoperative Pain

Abstract: The genetic variant of the COMT rs4680 single nucleotide polymorphism is associated with variability in opioid consumption in postoperative nephrectomy patients. The COMT rs4818 polymorphism may prove useful in predicting emesis medication use postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 18 publications
4
30
0
5
Order By: Relevance
“…Various clinical studies have demonstrated that the required dose of morphine is higher in subjects with a COMT G/G genotype, compared with other genotypes, in cancer and non-cancer pain (11)(12)(13)(14). The current findings are consistent with these results.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Various clinical studies have demonstrated that the required dose of morphine is higher in subjects with a COMT G/G genotype, compared with other genotypes, in cancer and non-cancer pain (11)(12)(13)(14). The current findings are consistent with these results.…”
Section: Discussionsupporting
confidence: 90%
“…In these studies, patients with the G/G genotype received the highest dose of morphine (11,12), while those with the A/A genotype received the lowest morphine dose (13). However, the majority of these studies had a small sample size, were retrospective, or were targeting non-cancer pain (14). A large sample study has indicated that none of the 112 single nucleotide polymorphisms (SNPs) in 25 candidate genes demonstrated significant associations with opioid dose (15); however, the quantity of concomitant analgesics [non-steroidal anti-inflammatory drugs (NSAIDs) and acetaminophen] and the method for dose determination of opioids remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Our results are also consistent with Candiotti and colleagues, who reported that individuals with the Val/Val genotype needed 36% more opioids than patients homozygous for the Met/Met group ( p = 0.009). However, they did not find significant differences among the three genotype groups for pain scores or emesis medication use in the first 24 h after surgery (Candiotti et al, 2014). …”
Section: Discussionmentioning
confidence: 95%
“…Genetic factors can also impact postoperative analgesic responses, which may impact CPSP since acute pain severity is among the strongest predictors of CPSP. In addition to multiple genes that impact drug metabolism [144], COMT [29,36] and OPRM1 [80,152] have been associated with postoperative opioid analgesic requirements.…”
Section: General Considerationsmentioning
confidence: 99%